Characterization of Organ-Specific Regulatory B Cells Using Single-Cell RNA Sequencing - Yang, Si-Yu; Long, Jie; Huang, Meng-Xing; Luo, Pan-Yue; Bian, Zhen-Hua; Xu, Ya-Fei; Wang, Cheng-Bo; Yang, Shu-Han; Li, Liang; Selmi, Carlo; Gershwin, M. Eric; Zhao, Zhi-Bin; et al. (Frontiers in Immunology, 2021)
Regulatory B cells (Breg) are considered as immunosuppressive cells. Different subsets of Breg cells have been identified both in human beings and mice. However, there is a lack of unique markers to identify Breg cells, and the heterogeneity of Breg cells in different organs needs to be further illuminated. In this study, we performed high-throughput single-cell RNA sequencing (scRNA-seq) and single-cell B cell receptor sequencing (scBCR-seq) of B cells from murine spleen, liver, mesenteric lymph nodes, bone marrow and peritoneal cavity to better define the phenotype of these cells. Breg cells were identified based on the expression of immunosuppressive genes and IL-10 producing B (B10) cell related genes, to define B10 and non-B10 subsets in Breg cells based on the score of the B10 gene signatures. Moreover, we characterized 19 common genes significantly expressed in Breg cells, including Fcrl5, Zbtb20, Ccdc28b, Cd9, Ptpn22, and further analyzed the transcription factor activity in defined Breg cells. Last, a BCR analysis was used to determine the clonally expanded clusters and the relationship of Breg cells across different organs. We demonstrated that Atf3 may potentially modulate the function of Breg cells as a transcription factor and that 7 organ-specific subsets of Breg cells are found. Depending on gene expression and functional modules, non-B10 Breg cells exhibited activated TGF-β pathway, thus suggesting that non-B10 Breg cells have specific immunosuppressive properties different from conventional B10 cells. In conclusion, our work provides new insights into Breg cells and illustrates their transcriptional profiles and BCR repertoire in different organs under physiological condition.